تحليل العوامل الداعمة لتحقيق أهداف تدريس النحو في الصف الثامن بالمدرسة المتوسطة الإسلامية حفظ القرآن مؤسسة المركز الإسلامي سومطرة الشمالية ميدان - Harahap, Uswatun Hasanah; Pujiati, Pujiati; Triadi, Fian (ANWARUL, 2024)
This research aims to find out the factors supporting the achievement of the objectives of teaching grammar in the eighth grade of the Islamic Middle School Quran memorization Foundation of the Islamic Center of North Sumatra Medan. The intentional approach is qualitative research. The results are that the supporting factors for achieving grammar teaching goals more influential is sincerity of intent. Because sincerity of intention will facilitate matters related to teaching Other supporting factors are the method used in good teaching with a beautiful principle, encouragement by the teacher, the intelligence of the students, a high desire in the hearts of the students to study and a capable teacher with the subject that he has reached. The method used is standard and inductive.